القائم بالإدارة في شركة المساهمة البسيطة - قريرة, تسنيم (University of Eloued جامعة الوادي, 2023)
يعدّ موضوع القائم بإدارة شركة المساهمة البسيطة موضوع السّاعة في التشريع الج ا زئري نظ اً ر لحداثة هذا النوع من الشركات الذي نصّ عليه المشرع في التعديل الأخير للقانون التجاري بمقتضى القانون رقم 22 09 المؤرخ في 05 ماي 2022 . يكتسي القائم بإدارة شركة المساهمة الب سيطة مرك اً ز قانونيا است ا رتيجيا داخل الشركة، إذ يعدّ العمود الأساسي في إدارة الشركة والمرآة العاكسة لها في مواجهة الغير. ومن أجل تمكين القائم بإدارة شركة المساهمة البسيطة من أداء مهامه بالشكل المطلوب، منحه المشرع مجموعة من الصلاحيات وحمّله مقابلها مسؤولية كل فعل يخرج من نطاقها ويؤدي إلى المسّاس بالمصلحة العامة للشركة.The topic of manager in the charge of a simple joint stock company is considered a recent topic in the Algerian legislation due to the modernity of this kind of companies. It was stipulated by the legislator in the last amendment to the Commercial Code according to Law No. 22_09 of 05th May 2022 . The manager of a simple joint-stock company occupies a strategic legal position within the company, as s/he is considered the main manager in the management of the company and its reflective mirror in the face of others . In order to enable the manager of a simple joint-stock company to perform his/her duties as required, the legislator granted him/her a set of powers and held him/her in exchange for responsibility for every act that goes beyond its scope and leads to violating the public interest of the company. Keywords: the person (manager) in charge of a simple joint stock company, Law No. 22_09, civil and penal liability, monitoring the work of the person managing a simple joint stock company.
مذكرة ماستر
Keywords: القائم بإدارة شركة المساهمة البسيطة، القانون رقم 22 _ 09 ، المسؤولية المدنية والج ا زئية، الرقابة على أعمال القائم بإدارة شركة المساهمة البسيطة .; Managing the Simple Joint Stock Company, Law No. 22-09, Civil Liability and Territorial Activities, Control over the work of the person managing the simple joint stock company